Analysis of Infrastructure for Covid-19 Patient Satisfaction at RSDI Banjarbaru City - Azhar; Yakin, Rahimul; Rizany, Ichsan; Adawiyah, Robiatul; Fikri, M.Khairul (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Patient satisfaction is a condition of fulfilling the wishes, expectations and needs of patients. Bases on datafrom March 2020 to March 2021, there was an increase in patients returning home at their own request by3% and the lack of fulfillement of patient satisfaction values which were still below 90%. The aim of thisstudy is to evaluate Infrastructure and compliance of covid-19 patients. The study desing used was crosssectional, whit a consecutive sampling and a sample size of 120 covid-19 patients. Data were analyzed usingthe spearman rank rest. Data collection was carried out from June 2021 to August 2021. The result of thestudy found that there was a relationship between phycsical facility and satisfaction with p value 0,001 and r0,498. The better infrastructure provide, the higher pastient satisfaction